Manufacturing a Robotic Arm Prototype for Minimally Invasive Surgeries - Aziz, Bahaa Al-Din Rokan; Hussein, Rana Alaa Nasser; Ahmed, Safa Mahdi Ali; Mohammed, Omar Ali Jassim; Deeb, Hussein Wathiq Muhammad (American Journal of Botany and Bioengineering, 2025)
In conclusion, the design and development of the 6DOF robotic arm of small surgical operations appear enormous to provide advanced and effective health care. Through accuracy tests and duration, arm performance has been evaluated and analyzing the results to determine which areas can be improved. This technique is an important development in medicine, where they can improve accuracy, speed and efficiency in surgical operations. With more development and improvement, robotic arm can become a valuable and effective solution in small and minute surgery. The development of robotic arms for small surgical operations requires closely interaction between mechanical engineers, software and doctors, to ensure reliable and precise performance. Thanks to advanced technology and continuous innovation, robotic arm can play a major role in improving surgical results and reducing risk in surgical operations. As research and development continues in this area, more progress and innovations can be expected in the field of design and use of future robotic arm, promoting health care and improving the quality of life for patients.